Trends of Educational Research in the International context - Juliana Raffaghelli (Pensa MultiMedia, 2014)
This position paper analyses some trends of educational research in the international context, as well as in relation with social and human sciences research, taking into account main dissemination publications and activities of organisms controlling both policy making and funding for Educational Research in the EU and USA. This analysis is undertaken with the aim to support comparative perspectives of educational research, focusing some key issues, forthcoming sceneries and critical aspects that will shape activities and training of educational researchers.